Effect of Grape Seeds Ethanolic Extract on Spatial Memory in Mice - Ali M. Ghazi (Journal of Global Pharma Technology, 2019)
Grape (Vitis vinifera) is a member of vitaceae family. The seeds are rich in polyphenols and phenolic acids that are not only safe to be consumed, but also recognized to produce several and meaningful health benefits. We aimed here to investigate the memory and learning processes (spatial memory) activity of the ethanolic extract of the grape seeds by using Morris Water Maze (MWM) test in laboratory mice. The present study revealed that the administration of ethanolic extract of Vitis vinifera (50 mg/kg, IP for 3 days) showed significant reduction to the escape latency using the MWM especially in the 4th and 5th day of experiment when the results were compared to the control group.  Conclusion: grape seed extract may behave as a memory stimulant that opens doors to use it medically as a supportive therapy in case of impaired memory functions.Keywords: Vitis vinifera, Spatial memory, Morris Water Maze.